Electrical conductivity and fiber orientation of poly(methyl methacrylate)/carbon fiber composite sheets with various thickness - Luo, Xiaoling; Qu, Muchao; Schubert, Dirk W. (Polymer Composites, 2020)
Poly(methyl methacrylate) (PMMA) composites containing carbon fibers (CFs) with the controlled aspect ratio (AR) at various concentrations were produced and hot pressed into rectangular sheets with a variety of thickness. The orientation of CFs on the surface and inside the specimen was obtained, and the conductivity σ in three different directions (X-length, Y-width, Z-thickness) were investigated. A preferential orientation of CFs in XY plane was found inside the samples, resulting in higher σX and σY. The orientation of CFs in Z direction increases with the sample thickness increasing, leading to an increasing σZ. Thus the anisotropic conductivity between σX (or σY) and σZ reduces from three orders of magnitude to one order of magnitude. The percolation thresholds (Φc) in three directions of the samples were revealed by fitting with McLachlan GEM equation, which lead to Φc,X ≈ Φc,Y ≈ Φc,Z, independent of the thickness and the measuring direction. The values of exponent t in GEM equation were found to be tX > tY > tZ, while tZ increases with the sample thickness. For the first time, the relationship between the exponent t and the sample thickness was revealed and discussed.
CRIS-Team Scopus Importer:2020-10-30
Keywords: anisotropic; carbon fibers; electrical conductivity; orientation; thickness